PROBLEMS IN SUBSIDARY FARMING ESPECIALLY IN CASE OF A VILLAGE SITUATED NEAR A MINE - DEPT. of GEOGRAPHY, OKAYAMA UNIVERSITY (Japanese Journal of Human Geography, 1962)
Yuka-mura, a farm village in Okayama pref., south-western Japan, is situated near a mine named Yanahara. Naturally, the most village-men are drawn to work at the mine instead of their own farm, so the farming must be leave to the care of their wives and their old parents, thus in this village the subsidary farming is deemed low productivity. By interviewing with selected 60 families…20% of all the farm families…author was able to clarify the following points: (1) Salary from the mining company is not enouth to make a living, so the villager think it indispensable to keep their farm for ever. (2) But the farm is so small in area…44 are in average…that the villager is unable to cultivate fruits or to rear cattle, they grow only paddy there. (3) Two sources of income…one from the mine, the other from the farm…are gratifying for them now, but at the same time they are worrying on future profession of their children. In order to have more chance in good job, they have to move to the city. (4) No villager agree to sell their farm because it is no doubt that the farm is their last means of living after retiring from their job. To keep farm means to keep their guarantee of living. The labor market in Japan is rather unstable now. In these points author indicate the dead-lock against the agrarian policy of Japanese government to improve the farming productivity by making adequate size of the farm and by keeping good labor supply.